2020
DOI: 10.5194/acp-20-11809-2020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular understanding of the suppression of new-particle formation by isoprene

Abstract: Abstract. Nucleation of atmospheric vapours produces more than half of global cloud condensation nuclei and so has an important influence on climate. Recent studies show that monoterpene (C10H16) oxidation yields highly oxygenated products that can nucleate with or without sulfuric acid. Monoterpenes are emitted mainly by trees, frequently together with isoprene (C5H8), which has the highest global emission of all organic vapours. Previous studies have shown that isoprene suppresses new-particle formation from… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 50 publications
12
66
1
Order By: Relevance
“…However, this may be an over-prediction of the emissions as, on some occasions, demonstrated by our chamber measurements, winter BVOC emission may be very low or absent from this species. Similarly, rain events have been shown to alter BVOC emissions and may have different effects in the short term (increasing) and the longer term (decreasing), which are also not accounted for in the model (Holzinger et al, 2006). These factors are likely to lead to an overestimation of emissions from all species but in particular Sitka spruce on a per annum basis.…”
Section: Uncertainties In Measured and Modelled Fluxesmentioning
confidence: 99%
“…However, this may be an over-prediction of the emissions as, on some occasions, demonstrated by our chamber measurements, winter BVOC emission may be very low or absent from this species. Similarly, rain events have been shown to alter BVOC emissions and may have different effects in the short term (increasing) and the longer term (decreasing), which are also not accounted for in the model (Holzinger et al, 2006). These factors are likely to lead to an overestimation of emissions from all species but in particular Sitka spruce on a per annum basis.…”
Section: Uncertainties In Measured and Modelled Fluxesmentioning
confidence: 99%
“…In the present study, we derived three compound vegetation properties -GPP, LAI and SCT -to evaluate the impact of BVOC sources on NPF event occurrence in urban environments. These three parameters can indirectly also be associated with vegetation emissions and finally with BVOC concentrations (Hidy et al, 2016). They were computed by the Biome-BGCMuSo biogeochemical model (v6; Thornton and Rosenbloom, 2005;Hidy et al, 2016).…”
Section: Vegetation Properties Related To Emissionsmentioning
confidence: 99%
“…These three parameters can indirectly also be associated with vegetation emissions and finally with BVOC concentrations (Hidy et al, 2016). They were computed by the Biome-BGCMuSo biogeochemical model (v6; Thornton and Rosenbloom, 2005;Hidy et al, 2016). This is a widely used, process-based model with a multilayer soil module that simulates the storage and flux of H 2 O, C and N between terrestrial managed agroecosystems and the atmosphere.…”
Section: Vegetation Properties Related To Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…mean transmission efficiency through the mass filter? If so, did the authors correct for this as shown in (Heinritzi et al, 2020;Zhao et al, 2010)? Also, the authors mention that the CIMS were calibrated for sulfuric acid concentration but how did they determine concentrations of the larger clusters?…”
mentioning
confidence: 98%